Preliminary study on associated risk factors of mortality due to COVID-19 pandemic in Malaysia - Mohd Shahrol Abd Wahil; Mohd Hasni Jaafar; Rohaya Ismail; Chua, Su Peng; Chandrika Jeevananthan; Rakesh Singh Sandhu; Mohd Faizal Madrim; Ammar Amsyar Abdul Haddi (MDPI, 2021)
The COVID-19 pandemic has claimed numerous lives worldwide. Malaysia documented about 118 mortalities during the second wave of the outbreak. This study aims to assess associated risk factors of the COVID-19 mortalities from 18 March until 22 May 2020. The majority of patients were above 60 years old (69.0%), male (78.0%), and Malaysian citizens (98.0%). The mean age of the mortalities was 64.01 years old (±SD 14.91 years). The major risk factors consist of hypertension (52.0%), diabetes mellitus (43.0%), cardiovascular diseases (21.0%), extra-pulmonary solid malignancies (5.0%), cerebrovascular diseases (3.0%), pulmonary diseases (1.0%) and pulmonary malignancies (1.0%). About 23.0% of mortalities were related to established clusters while 5.0% had a history of travelling overseas. The mean survival time was 11.87 days (±SD 9.32 days). Approximately 50.0% of the patients survived until day 10 post-admission. The probability of the patients surviving beyond 30 days post-admission was less than 10.0%. There is a significant difference between groups for having a shorter duration to death for risk factors including age group, history of travelling overseas, attending mass gatherings, and having pulmonary malignancies. The hazard ratio (HR) for pulmonary malignancy is 5.512 (95% CI 0.662, 45.899), mass gathering; 3.434 (95% CI 1.375, 8.579), pulmonary disease is 2.442 (95% CI 0.314, 18.983), travelling overseas; 2.251 (95% CI 0.657, 7.711), extra-pulmonary solid malignancy; 2.165 (95% CI 0.767, 6.112), and despite the significant result only applied for mass gathering (p-value = 0.008). COVID-19 screening should be mandatory for those who attend mass gatherings as they are the main source of COVID-19 spread in the community during the second wave outbreak in Malaysia